Implementation of Solution-Focused Brief Counseling to Increase the Resilience of Victims of Sexual Harassment - Apriana Putri, Ria; Kusnadi, Kusnadi; Fitri, Hartika Utami (Scidacplus, 2023)
This study entitled the application of Individual Counseling with a Solution-Focused Brief Counseling Approach to Increase the Resilience of Victims of Sexual Harassment (Case Study of Client